2020
DOI: 10.1042/bst20190535
|View full text |Cite
|
Sign up to set email alerts
|

Small molecules that target the ubiquitin system

Abstract: Eukaryotic life depends upon the interplay between vast networks of signaling pathways composed of upwards of 109–1010 proteins per cell. The integrity and normal operation of the cell requires that these proteins act in a precise spatial and temporal manner. The ubiquitin system is absolutely central to this process and perturbation of its function contributes directly to the onset and progression of a wide variety of diseases, including cancer, metabolic syndromes, neurodegenerative diseases, autoimmunity, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 143 publications
0
30
0
2
Order By: Relevance
“…To date, there is only one type of FDA-approved drug targeting an E3 ligase and several candidate compounds that have advanced into clinical trials [45,54]. This class of FDA-approved drugs is the thalidomide compounds that target cereblon (CRBN), a protein that operates in the E3 ligase complex CRL4 [55,56].…”
Section: Current Status Of E3 Ligase Therapeutic Developmentmentioning
confidence: 99%
“…To date, there is only one type of FDA-approved drug targeting an E3 ligase and several candidate compounds that have advanced into clinical trials [45,54]. This class of FDA-approved drugs is the thalidomide compounds that target cereblon (CRBN), a protein that operates in the E3 ligase complex CRL4 [55,56].…”
Section: Current Status Of E3 Ligase Therapeutic Developmentmentioning
confidence: 99%
“…SOP11 and reduced thiolutin were found to also inhibit other JAMM metalloproteases, suggesting that additional optimization may be required for improved Rpn11 specificity. A more extensive review of these inhibitors can be found in [172,173].…”
Section: Accepted Articlementioning
confidence: 99%
“…The screening of compounds for effects on protein ubiquitination and deubiquitination has led to the identification of a number of E3 ubiquitin ligase- and DUB-targeting drugs [ 29 , 165 , 177 ]. Because the substrates of these enzymes have a wide variety of functions, such drugs can interfere with various signaling pathways and impair physiological functions.…”
Section: Future Directionsmentioning
confidence: 99%
“…As noted, some of the E3 ubiquitin ligases and DUBs involved in the maintenance of ciliary protein stability may be therapeutic targets for the associated disorders. Indeed, small molecules targeting these E3 ubiquitin ligases and DUBs, including USP8, USP9X, CYLD, and VHL, have been successfully developed [ 29 , 177 , 186 ]. However, the role of E3 ubiquitin ligases and DUBs in disease can be context dependent [ 28 , 148 , 187 , 188 ].…”
Section: Future Directionsmentioning
confidence: 99%